Análisis de un repertorio bibliográfico sobre la encuadernación española. - Carpallo Bautista, Antonio (Revista General de Información y Documentación, 2002)
Up to the publication of the book titled Documental Analysis of Spanish Binding there had been no research work which included the most important printed documents on Spanish binding. This work analyzes the bibliographical references included in the aforementioned book, focusing on the thematic areas, the documental typology, the production chronology, the most relevant periodical publications, the most important authors and the places and languages of publication.
Keywords: Bibliographic repertories; Spanish binding; Document analysis